THE EFFECTS OF SPORTS ON LIFE - Akmal Tajiddinovich Khalikov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In today’s world, sports form an integral part of the society’s culture. Participating in sports is an important aspect of child development that has many benefits. Sports improve the health status of participants and foster the development of fundamental skills that are important in facing challenges in life .Other benefits of sports include fostering social co-existence and peace, encouraging community development, financial gains and foster international unity .Sports have made significant contributions in enhancing the implementation of certain policies that are important and that affect the welfare of the society. Healthy human development is a requisite for sustained societal development. Without a healthy population, it is impossible to achieve the goals and objectives that stimulate growth and development. Therefore, it is necessary to maintain good health in individuals in order to enable them to use their potential to stimulate growth and personal development . Sport is an important tool that has the ability to motivate and empower individuals to achieve their health, economic and social goals.